2012
DOI: 10.1002/aqc.2264
|View full text |Cite
|
Sign up to set email alerts
|

Offsetting the impact of the marine ornamental trade: a case study of two temperate top shells (Osilinus lineatus and Gibbula umbilicalis) as potential clean‐up crew

Abstract: It is estimated that several million tropical gastropods are exported each year for the marine ornamental trade to become part of a clean‐up crew (those species that have a beneficial function such as controlling nuisance algae) in an aquarium. Collecting non‐tropical species could offset exploitation impacts, reduce shipping costs and increase survival rates due to shorter transport distances. However, these species must be able to survive and function at tropical marine tank temperatures (25 °C). Two species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…Previous experiments have shown that competition for food can cause higher mortalities [ 35 37 ] and was suggested by Watson et al [ 18 ] as a driver for differential species mortality in two temperate trochids. The potential explanation for differences in mortality here is unlikely to be food as it was provided in excess through regular replacement of the stones.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous experiments have shown that competition for food can cause higher mortalities [ 35 37 ] and was suggested by Watson et al [ 18 ] as a driver for differential species mortality in two temperate trochids. The potential explanation for differences in mortality here is unlikely to be food as it was provided in excess through regular replacement of the stones.…”
Section: Discussionmentioning
confidence: 99%
“…All three tropical species consumed nitrocellulose in the grazing experiment (compared to the background losses) at levels similar to Gibbula umbilicalis and P . lineatus [ 18 ]. Results show that T .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations